Clinical relevance of the hip joint: Part I – Review of the anatomy of the hip joint. (November 2015) - Sato, Tomonori; Sato, Naomi
Abstract : The hip joint is a complex anatomic structure composed of osseous, ligaments, and muscular structure. It is a unique joint because it provides both stability and multiaxial mobility, and is involved in transferring the weight of the body. It is a common site of osteoarthritis (OA). OA is believed to be the most prevalent chronic joint disease of the hip joint and its incidence is rising as the population ages. A thorough anatomical understanding of the hip joint may us help to improve the management of hip conditions, including OA. This article presents a review of anatomy of the hip joint, designed to help a better understanding of the principles of management. We also discuss the clinical importance of anatomy of this joint from the perspective of conservative treatment.